LITERATURE REVIEW ON THE IMPACT OF INNOVATIVENESS ON SUPPLY CHAIN MANAGEMENT - Aminu, Yusuf; Albasu, Hafsat Bashir; Yahaya, Ali Ukashatu (Kashere Journal of Management Sciences, 2025)
The paper aims to address the vital issues of supply chain management, examining the managerial strategies that can enable businesses to withstand disruptive events and rebound from challenges with agility and minimal impact. Within these discussions, innovative strategies capable of elevating logistics and supply chain managerial efficiency, advancing green initiatives, and ensuring that these complex networks can manifest ever everlasting solution to supply chain issues. The study aims to describe the impact of innovativeness on supply chain management: A Literature Review. Methodologically, A literature review is conducted to identify and analyze publications in peer-reviewed academic journals that include contributions from different strands of management research. This paper analyzes the theoretical contributions of the supply chain literature using Gregor’s (2006) framework of theory classification. It also evaluates the levels of analysis of the literature using the structural view model proposed by Skinner et al. (2006). Findings show that this research identified and analyzed various topics related to the supply chain innovation construct and showed that supply chain innovations can be studied at multiple analytical levels. The identification and analysis of relevant articles highlighted the need to conceptualize the supply chain innovation construct and develop measurement scales to operationalize it. In conclusion, the result can be applied to the decision-making process of managers regarding supply chain innovations.